(untitled) (Journal of Accessibility and Design for All, 2024)
Transport infrastructures are fundamental elements to achieving social cohesion, territorial development and the productive growth of society, but they must be accessible, sustainable, resilient and of high quality. There are several plans at the local and European levels that address strategies and directives to achieve inclusive public transport that adheres to the parameters of sustainability and accessibility. Therefore, in this work we have conducted a study and analysis of the situation of intercity regular bus public transport in Spain. In addition to carrying out an exhaustive bibliographic review on the importance and interest of public transport and accessibility, we also reviewed companies in the sector in order to reinforce our research. A survey of different groups of people, with and without disabilities, was performed to provide a broad and diverse view of the problems and advantages of public bus transport. The advances and challenges of using this means of transport for the mobility of people and its importance to improving society have been analysed. This research seeks to extract an in-depth analysis - through a review of the literature and surveys of 82 people - of the accessibility chain in regular bus lines in Spain, and to offer proposals and recommendations that can help the main stakeholders in the sector to offer accessible, inclusive and quality transport.